The Transitivity Shift in the Translated Official Website of Indonesian Ministry of Health - Zuhera, Delia (Politeknik Harapan Bangsa Surakarta, 2021)
The objectives of this research are to depict the shift of transitivity that happen brought about by applying interpretation strategies in the translation on the site of Indonesian Ministry of Health. This research is Transitivity Shift In The Translated Official Website Of Indonesian Ministry Of Health. The samples of the research were clauses under the classification of experiential capacity that experience a shift in transitivity. The data were gathered by using the observation strategy. This strategy specifically selects articles that regulate Covid-19 and their translations in English. It has to carefully read every provision in the source language, then finding transitivity shifts by grouping it according to the experience capacity function. This research was analyzed by qualitative descriptive method and Systemic Functional Linguistic (SFL) approach. The findings showed that there are the transitivity shifts in the articles that published on 20th July and 11th September 2020. In conclusion, the transitivity shift in the analyzed articles, there are transitivity shifts on existential to verbal, material to relational, behavioral to material, verbal to relational and relational to existential. Nonetheless, there is no shift involving mental process in the two articles.